The Significance of the Works of Professor Yu. Ya. Baskin for the Development of Legal Science in Russia - K. K. Lebedev (Теоретическая и прикладная юриспруденция)
The essay is devoted to the analysis of the works of Professor Yu. Ya. Baskin and the substantiation of the great contribution he made to the development of domestic legal science.